Analysis Of The Responsibility Of Insurance Companies Declared Bankrupt For Customer Claims In The Perspective Of Indonesian Positive Law - Dela Rezki Silfia; Kitfiyatun Nisah; Salsabila Dito Putri; Harmono Harmono; Raden Handiriono (Journal Of Social Science (JoSS), 2024)
Insurance for human life is very important, by requiring a sense of comfort and safety. So that many companies have established their business in the field of insurance, behind insurance companies that provide security protection. Not all companies run smoothly in other words the company is inseparable from the threat of bankruptcy. This research focuses on legal certainty for customers when an insurance company with claim obligations is declared bankrupt. The research problem addresses the challenges faced by customers in such situations and the legal protection available to them. The purpose of this research is to find out the responsibility of insurance companies that are declared bankrupt in fulfilling customer claims and to find out the legal certainty for customers in cases when insurance companies that have claims obligations are declared bankrupt. The methodology used is normative juridical, by analyzing the law based on literature study, articles in the Civil Code, Law Number 21 of 2011 concerning OJK, Law Number 37 of 2004 concerning Bankruptcy and postponement of debt payment obligations, and Insurance Law. The results discuss the importance of legal protection provided by the Financial Services Authority and the Deposit Insurance Corporation for insurance customers in bankruptcy cases. The findings underscore the need for compliance with certain legal provisions to ensure customer protection, especially in cases involving insolvent insurance companies. The implications of this study emphasize the importance of legal certainty and the role of regulatory bodies in protecting customer rights in the insurance sector.